Placental abruption at 18 weeks of gestation: a rare case report - Sharma, Deepti; Gupta, Aakriti; Gupta, Ranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Placental abruption is one of several notable obstetrical entities that may be complicated by massive and sometimes torrential hemorrhage. Hypovolemic shock is caused by maternal blood loss. Delayed or incomplete treatment of hypovolemia with severe placental abruption can cause acute kidney injury, disseminated intravascular coagulation. Placental abruption is most commonly seen after 24 weeks of pregnancy and it is very rare before 20 weeks of pregnancy. Here, we report a case of life-threatening placental abruption at 18 weeks of gestation.